(untitled) (Research, Society and Development, 2022)
With the popularization of the World Wide Web and access to connected cell phones, there is a change in the ways of making payments, with the increasing use of applications. Online shopping also follows this trend. This revolution occurs unevenly between countries, within them and across different social classes, ages, genders, educational levels and quality of internet access. To understand how this process occurs in municipalities far from capitals, the behavior of consumers in Tefé, state of Amazonas, Brazil, was studied from interviews in the year 2021. It was verified whether they use payment applications or make purchases over the internet, as well as the degree of satisfaction with the internet offered in the city. In addition to recording the effect of demographic variables (age, education level and gender) on whether or not they have payment apps on their cell phones, or have made online purchases. It was observed that the population’s adherence to applications and purchases over the internet is still below those observed in Brazilian capitals and that there is discontent among the majority of the population regarding the quality of the internet offered by mobile operators in the city. The fact that consumers have a payment application on their cell phone was strongly influenced by their age, level of education and level of satisfaction with the internet in the city. Age, gender, and level of education influenced the probability of consumers having made purchases over the internet.